2003
DOI: 10.4049/jimmunol.170.5.2695
|View full text |Cite
|
Sign up to set email alerts
|

Anti-idiotype × Anti-LFA-1 Bispecific Antibodies Inhibit Metastasis of B Cell Lymphoma

Abstract: Abs to adhesion molecules can block tumor metastasis. However, they may also block the function of normal cells. To circumvent this adverse effect, we proposed the use of bispecific Abs that bind simultaneously to an adhesion receptor and to a tumor-specific Ag. Such Abs bind more avidly to tumor cells that coexpress both target Ags than to normal cells. The Id of the surface Ig of malignant B lymphocytes is a tumor-specific Ag. We therefore produced a bispecific Ab with specificity to the adhesion molecule LF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 38 publications
1
22
0
Order By: Relevance
“…Therefore, we studied the effect of the bispecific Abs on tumor cell migration. As previously reported by us (19) and by others (43), despite the massive development of 38C-13 lymph node metastases, only a small proportion of the i.v. injected cells migrated to peripheral and mesenteric lymph nodes, suggesting that the entry of a small number of lymphoma cells into lymph nodes is sufficient for development of metastases.…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…Therefore, we studied the effect of the bispecific Abs on tumor cell migration. As previously reported by us (19) and by others (43), despite the massive development of 38C-13 lymph node metastases, only a small proportion of the i.v. injected cells migrated to peripheral and mesenteric lymph nodes, suggesting that the entry of a small number of lymphoma cells into lymph nodes is sufficient for development of metastases.…”
Section: Discussionsupporting
confidence: 48%
“…Our in vitro studies demonstrated that the anti-Id ϫ anti-LFA-1 bispecific Ab selectively blocked LFA-1-mediated adhesion of Id-expressing tumor cells, but had no effect on adhesion of normal lymphocytes (14). Moreover, it abolished liver metastasis in tumor-bearing mice (19). However, despite its dramatic inhibitory effect on liver metastasis, the anti-Id ϫ anti-LFA-1 Ab had only partial effect on dissemination to lymph nodes, and no effect on spleen and bone marrow metastasis.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…LSECs express and secrete ICAM-1, and tumor expression of LFA-1 integrin contributes to hepatic metastasis of lymphoma, leukemia, and breast cancer, 29,30 whereas LFA-1 blockade 31 and ICAM-1-deficient mice 32 can inhibit hepatic metastasis. At present, the role of LFA-1 expression by colon carcinoma cells is unclear, although CD44 induces HT-29 tumor cell adhesion and migration through LFA-1 up-regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-idiotype antibodies against a B cell lymphoma antibody, 38C-13, have been produced by using idiotype conjugated to keyhole limpet hemocyanin (306,307). Anti-idiotypes and bi-specific antibodies have been generated to be used as treatments for lymphomas (308,309). Bi-specific antibodies that bind to an adhesion receptor and tumor specific antigen at the same time are effective in blocking tumor metastasis.…”
Section: Future Directionsmentioning
confidence: 99%